Homicides and Suicides by Mentally Ill People. (2003) - Shahtahmasebi, Said
Abstract : In 1992, following consultations with the Royal College of Psychiatrists, the confidential inquiry into homicides and suicides by mentally ill people was set up by the United Kingdom Department of Health. The inquiry collects detailed information on contact with secondary mental health services by means of a questionnaire from clinical audit or information departments from these organisations. In Leeds, however, a wider range of available records including Coroner Reports, police, social, educational, and all health records were consulted. This resulted in a series of health/life event histories of suicide cases that had been in contact with psychiatric services. This paper presents an exploratory analysis of these data. The Leeds suicide cases formed less than one-third of all suicide cases in Leeds; the remainder had not come into contact with psychiatric services. This proportion is consistent with the U.K. national figures. Records show that 46% of the sample's first contact with the psychiatric services was through a first failed attempted suicide. Other results include the role of prescribed drugs in repeat suicide attempts, education levels, and employment stability. It is concluded that the link between mental illness and suicide is questionable. Life event history type data on all suicide cases is desperately required to study suicide as a social process.